2011
DOI: 10.1186/1471-2334-11-150
|View full text |Cite
|
Sign up to set email alerts
|

Anal and oral human papillomavirus (HPV) infection in HIV-infected subjects in northern Italy: a longitudinal cohort study among men who have sex with men

Abstract: BackgroundA study including 166 subjects was performed to investigate the frequency and persistence over a 6-month interval of concurrent oral and anal Human Papillomavirus (HPV) infections in Human Immunodeficiency Virus (HIV)-infected men who have sex with men (MSM).MethodsPatients with no previously documented HPV-related anogenital lesion/disease were recruited to participate in a longitudinal study. Polymerase chain reaction (PCR) was performed to detect HPV from oral and anal swabs and to detect Human He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
75
3
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 47 publications
18
75
3
4
Order By: Relevance
“…Men are key to the transmission of HPV to women, but relatively little is known about the natural history of HPV infection in men (3). The prevalence of HPV in males ranges from 7% to 45% (4), but the majority of studies have been conducted on homosexuals, HIV patients or infertile men (5,6). Recently, Klinglmair et al found a high prevalence of HPV infection in a cohort of 250 young males, including children (0-10 years), indicating non-sexual transmission pathways (7).…”
Section: Introductionmentioning
confidence: 99%
“…Men are key to the transmission of HPV to women, but relatively little is known about the natural history of HPV infection in men (3). The prevalence of HPV in males ranges from 7% to 45% (4), but the majority of studies have been conducted on homosexuals, HIV patients or infertile men (5,6). Recently, Klinglmair et al found a high prevalence of HPV infection in a cohort of 250 young males, including children (0-10 years), indicating non-sexual transmission pathways (7).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, HPV58 and 52, which are common type in Japanese women, were considerably prevalent in the anus of the Japanese MSM population. In addition to HPV6 and 16, HPV51 and 58 were also relatively frequent in South Africa [8], HPV11 and 61 in Italy [7], and HPV53 and 84 in Spain [9]. The distribution of HPV types is likely to slightly differ between different regions and populations.…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiological studies have been conducted to investigate anal HPV prevalence among HIV-infected MSM in several countries and regions. Anal HPV prevalence in HPV-infected MSM was 61.0% of 92 patients in the United States [3], 74.2% of 140 in Spain [4], 75.9% of 361 in Japan [5], 82.7% of 133 in Korea [6], 88.6% of 166 in Italy [7], 91.8% of 85 in South Africa [8], and 95.5% of 1439 in Spain [9]. The high prevalence of anal HPV infection observed in the present study is similar to that previously reported in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…La infección por VPH en población infectada por VIH es mucho más frecuente que en población general; así, en mujeres con infección por VIH la prevalencia de co-infección cervical por VPH se multiplica por tres respecto a las sin infección por VIH. Este aumento en la prevalencia es mucho más acusado en varones, especialmente en HSH seropositivos para VIH, donde la prevalencia de infección anal por VPH asciende a 89% en algunas series 45 . Además de una mayor prevalencia, los pacientes infectados por VIH tardan más en aclarar la co-infección por VPH lo que se relaciona al mayor número de procesos neoplásicos asociados a este virus en población seropositiva para VIH.…”
Section: Neoplasias Definitorias De Sida Y Neoplasias No Definitoriasunclassified